2014
DOI: 10.1111/asj.12343
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between the behavior of recreational horses, the physiological parameters and summer atmospheric conditions

Abstract: The aim of this paper was to select atmospheric factors and their values, which may disrupt the correct behavior and physiological condition of recreational horses. The studies were carried out from 1 July until 1 September on 16 Anglo-Arabian geldings. Each day, from 09.00 to 10.00 hours, the horses worked under saddle. The riders and the authors gave a qualitative behavioral assessment for each horse. Mood and willingness to work were evaluated. The quantitative assessment was called 'incorrect behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
9
1
1
Order By: Relevance
“…This advantage means a drawback as well, as it occurs at a high energetic cost, making endothermic animals face a two-fold challenge. This double challenge could be one of the reasons, as reported by Janczarek et al [ 43 ], for adverse changes in the behavior of recreational horses that can occur if the horse is ridden when the air temperature is above 26 °C. These conditions may cause an alteration in mood, with donkeys showing more elusive and hyporeactive responses, and a reduction in the willingness to work in horses and other equids.…”
Section: Discussionmentioning
confidence: 99%
“…This advantage means a drawback as well, as it occurs at a high energetic cost, making endothermic animals face a two-fold challenge. This double challenge could be one of the reasons, as reported by Janczarek et al [ 43 ], for adverse changes in the behavior of recreational horses that can occur if the horse is ridden when the air temperature is above 26 °C. These conditions may cause an alteration in mood, with donkeys showing more elusive and hyporeactive responses, and a reduction in the willingness to work in horses and other equids.…”
Section: Discussionmentioning
confidence: 99%
“…; Janczarek et al . ). It was found that these parameters are more sensitive indicators of the general predisposition of leisure horses than behavioral observation, and may potentially be applied to improve the welfare of leisure horses as well as the safety of people.…”
Section: Introductionmentioning
confidence: 97%
“…Janczarek et al . () defined the threshold values for atmospheric factors in the summer season which, when exceeded, may trigger unfavorable changes in heart rate parameters, body temperature and mood in leisure horses. Unfortunately, papers on the desired motor traits in leisure horses are still lacking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations